NPF of Islamic Rural Banks in Indonesia: Do Socio-Economic Factors and Bank Performance Matter? - Rifky Zahrul Aprilian; Barianto Nurasri Sudarmawan (Journal of Islamic Economics and Finance Studies)
This study focuses on the analysis of socio-economic factors and bank characteristics that affect non-performing financing (NPF) in Islamic Rural Banks (BPRS) in Indonesia. The main problem raised is the high level of NPF which can threaten the financial stability of BPRS, even though financial inclusion continues to increase. The study uses the Panel Data Regression method, utilizing a sample of 139 BPRS registered with the Financial Services Authority (OJK) during the period 2015-2024. The results of the study show that economic inequality and operational efficiency have a significant effect on NPF, while the unemployment rate, GDP, and Financing to Deposit Ratio (FDR) do not show a significant effect. Capital Adequacy Ratio (CAR) and Return on Assets (ROA) are proven to have a significant impact on reducing the risk of non-performing financing. This finding emphasizes the importance of managing these variables to support the sustainability of BPRS in supporting financial inclusion and preventing the risk of bankruptcy.